2009
DOI: 10.1113/jphysiol.2009.177105
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional rapidly adapting mechanosensitive enteric neurons (RAMEN) in the myenteric plexus of the guinea pig ileum

Abstract: An important feature of the enteric nervous system (ENS) is its capability to respond to mechanical stimulation which, as currently suggested for the guinea-pig ileum, is encoded by specialized intrinsic primary afferent neurons (IPANs). We used von Frey hairs or intraganglionic volume injections to mimic ganglion deformation as observed in freely contracting preparations. Using fast voltage-sensitive dye imaging we identified rapidly adapting mechanosensitive enteric neurons (RAMEN, 25% of all neurons) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
108
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(124 citation statements)
references
References 40 publications
14
108
1
1
Order By: Relevance
“…Our earlier in vivo studies (7,22,23) and the present in vitro study clearly prove that the inhibitory motor neurons are indeed mechanosensitive. Our findings are in agreement with the concept of multifunctionality of myenteric neurons proposed by Schemann and colleagues (28,29), who demonstrated that a large number of myenteric neurons possess sensory, integrative, and motor functions in the same cell. Mechanosensitivity in a small number of NO synthase-containing interneurons of the myenteric plexus of the small intestine and colon in guinea pigs has also been reported (41).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our earlier in vivo studies (7,22,23) and the present in vitro study clearly prove that the inhibitory motor neurons are indeed mechanosensitive. Our findings are in agreement with the concept of multifunctionality of myenteric neurons proposed by Schemann and colleagues (28,29), who demonstrated that a large number of myenteric neurons possess sensory, integrative, and motor functions in the same cell. Mechanosensitivity in a small number of NO synthase-containing interneurons of the myenteric plexus of the small intestine and colon in guinea pigs has also been reported (41).…”
Section: Discussionsupporting
confidence: 82%
“…Sensory neurons are also called IPANs, which are defined on the basis of morphology (Dogiel type 2), electrophysiological behavior (afterhyperpolarization), and chemical coding (calbindin, neurofilament 145kD, and calretinin positivity) in guinea pig and mouse small intestine and colon. However, there is considerable debate about whether IPANs are truly sensory neurons, because mechanosensitivity has been found in a large number of enteric neurons of the mouse/guinea pig small and large intestine (colon), even when these cells are not consistent with the morphological description, electrophysiological behavior, and chemical coding of IPANs (28,29,41). Furthermore, stretch-activated reflexes exist in the stomach, where there are no IPANs (41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, our results show that expression of MrgE and MrgF is not limited to IPANs. A recent study revealed that mechanosensitivity is a property of more enteric neuronal subpopulations than generally assumed and that every subpopulation of enteric neurons is to some extent sensitive to mechanical distortion, which might imply that the current concept of sensory transmission in the ENS needs to be revised (Mazzuoli and Schemann 2009). In previous studies in rat, MrgA, MrgC and MrgF mRNAs were detected in the cerebellum, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…It has been more recently discovered that distortion also excites other neurons, for example interneurons, in the enteric nerve circuits [79][80][81], indicating that reflexes are not uniquely initiated or modulated through type II neurons. Cell bodies of multi-axonal IPANs are 10-30 % of neurons in the submucosal and myenteric ganglia of the small and large intestines.…”
Section: Intrinsic Sensory Neurons (Ipans)mentioning
confidence: 99%